A Comprehensive Business Plan for SERENE ORGANIC UNISEX SPA AND SALON - KARUNAKARAN, ARUN JOHN (2015)
SERENE ORGANIC UNISEX SPA and SALON is a premium spa and salon brand aimed at giving its guests an experience of a lifetime with its natural yet soothing organic spa services and maintaining wellness through a series of well organised beauty salon services.